Pengaruh Kualitas Pelayanan, Harga, dan Promosi Terhadap Kepuasan Pelanggan (Survei pada Pelanggan Warmindo Riverside Surakarta) - Ardiya Putra, Oka; Pratiwi, Adcharina (Teewan Journal Solutions, 2025)
Warmindo Riverside Surakarta is one of the Indomie restaurants located at Jalan Popda No.10 Nusukan, Kecamatan Banjarsari, Central Java. Founded by Siti Aminah in 2020, the place can be described as Instagrammable due to its elegant and aesthetic interior. This research aims to examine the significance of service quality, price quality, and promotion on customer satisfaction at Warmindo Riverside Surakarta. This study uses both qualitative and quantitative research methods. The data source used is primary data collection. The population in this study are all customers of Warmindo Riverside Surakarta, with an unknown exact population number. The sampling technique used is non-probability sampling (purposive sampling) with a sample size of 100 respondents. Data analysis uses multiple linear regression analysis, t-test, F-test, and coefficient of determination (R2). The results of the validity and reliability tests show that all statements regarding service quality, price, and promotion are declared valid because the p-value < 0.05 and reliable because Cronbach's alpha > 0.60. The results of the classical assumption test show that all variables have passed the multicollinearity, autocorrelation, heteroscedasticity, and normality tests. The results of the multiple linear regression analysis obtained the equation Y = 4.517 + 0.148 X1 + 0.533 X2 + 0.319 X3 + e. The results of the t-test show that service quality (X1) has a significant effect on customer satisfaction at Warmindo Riverside Surakarta, price (X2) has a significant effect on customer satisfaction at Warmindo Riverside Surakarta, and promotion (X3) has a significant effect on customer satisfaction at Warmindo Riverside Surakarta. The results of the F-test show that the regression model used in this study is appropriate. The results of the coefficient of determination (R2) test show that the independent variables contribute 40.6% to the dependent variable, while the remaining 59.4% is influenced by factors outside the variables studied.